Peran kalsium sebagai prevensi terjadinya hipoplasia enamel (The role of calcium on enamel hypoplasia prevention) - Soegeng Wahluyo (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2013)
Background: Fluoride is a trace element found in many natural and commonly consumed by humans in the form of fluoride salts such as Sodium Fluoride (NaF). The impacts that are most often caused by the intake of fluoride is a damage of enamel tooth/enamel hypoplasi or fluorosis. The manifestations of these effects are defects in teeth with whitish colour, brown to black colour effected on the aesthetic. So that the prevention of fluorosis is required. Purpose: The aim of this study was to analyze the effect of calcium as prevention against tooth enamel fluorosis in Wistar rats caused by exposure to fluoride through indicators of Amelogenin, Calbindin- 28kDa protein expression, the matrix of tooth enamel density and distance between ameloblast cell. Methods: This was an experimental studies, post-test only control group design. This study used three groups of rats. Group 1 (Control) was induced by sterile destilled water, group 2 (treatment 1) was induced by fluoride and group 3 (treatment 2) was induced by combination of fluoride and calcium. Each induction was done through sonde for 28 days. results: The results showed that the induction of fluoride causes the increased expression of Amelogenin protein; decreased expression of Calbindin-28kDa protein; a decrease in the density of the enamel matrix and widen the distance between cells ameloblast, while the result of the combination induced by fluoride and calcium showed increased protein expression of Calbindin-28kDa and increased density of the enamel matrix. Conclusion: Calcium can be used as an alternative preventive against the occurrence of enamel hypoplasia due to exposure of fluoride in Wistar rats.latar belakang: Fluorida adalah salah satu trace element yang ada dialam dan sering dikonsumsi manusia dalam bentuk garam fluorida yaitu sodium fluoride (NaF). Paparan fluorida biasanya berkaitan dengan asupan fluorida yang dapat membahayakan enamel gigi yaitu terjadinya hipoplasia enamel atau fluorosis. Manifestasi efek ini memberikan gambaran berupa defect pada enamel gigi ditandai dengan perubahan warna dari kecoklatan hingga kehitaman dan penyebab estetik yang tidak baik, maka diperlukan usaha pencegahan fluorosis tersebut. tujuan: Studi ini adalah menganalisis efek kalsium terhadap prevensi terjadinya fluorosis pada tikus Wistar yang terpapar fluorida, dengan indikator ekspresi protein Amelogenin, Calbindin-28kDa, densitas matriks enamel dan jarak antar sel ameloblas. Metode: Studi ini merupakan studi eksperimental dengan desain Post Test Only Control Group, yang menggunakan 3 kelompok tikus. Kelompok-1 (kontrol) di induksi dengan aquadest steril, kelompok-2 (treatmen-1) diinduksi dengan fluorida dan kelompok-3 (treatmen-2) diinduksi dengan kombinasi antara fluorioda dan kalsium. Induksi dilakukan selama 28 hari melalui sonde. hasil: Menunjukkan bahwa induksi dengan fluorida menyebabkan peningkatan ekspresi protein Amelogenin dan terjadi penurunan ekspresi protein Calbindin-28kDa, dan penurunan kepadatan matriks enamel serta pelebaran jarak antar sel. Tetapi bila diinduksi dengan kombinasi fluorida dan kalsium maka terjadi peningkatan ekspresi Calbindin-28kDa dan peningkatan densitas matriks enamel. Simpulan: Kalsium dapat digunakan sebagai alternative terhadap terjadinya hipoplasia enamel akibat paparan fluorida pada tikus Wistar.